”Non soltanto un giallo politico”: Leonardo Sciascia e la sua ricezione in Ungheria - Antonio Sciacovelli (Casa Editrice Leo S. Olschki, 2022)
The reconstruction of the reception of Leonardo Sciascia's lifework in Hungary, from the early 60s of the 20th century to the present years, is deeply related to the last decades of the cultural life in the Danubian country. The analysis of translations (in volume or in literary magazines), of the studies relating to literary issues, including the presentation of themes, perspectives and discussion about the main elements of the detective stories, until the relief of the importance of the cinematographic adaptations of his works, strongly testifies a constant interest for the works of the Sicilian writer, from the point of view of his "popular" diffusion and as the object of the possible perspective from the "things of Sicily" and Italy, to the understanding of few moments and events of the history of Hungary.